THE TOPPLING OF AN IRRIGATION CENTER PIVOT SUBMITTED TO WIND ACTION EFFECTS - Schmidt,Edomir M. (2019)
ABSTRACT This research aims to improve the study about the stability of truss structures used in pivot irrigation, widely used due to the growing demand for food production, when submitted to wind effects. Specifically, it aims to verify the maximum wind speed supported by an irrigation center pivot structure when submitted to the load effects caused by wind gusts perpendicular to the equipment. In order to determine these forces and their effects on the irrigation equipment, computational numerical investigations were carried out using finite element bar models validated by measuring the natural frequency of the equipment in the field. A span was designed based on the existing standards in Brazil and the dynamic response of the structure was examined under the effects of wind gusts. Models of the Brazilian standard NBR 6123/88 for structures submitted to wind effects were used in this study. The studied irrigation equipment supports wind gusts of up to 115 km/h applied perpendicularly, with a duration of 3 s, before generating toppling.